An Integrated Approach for ECG Compression and Encryption in E-healthcare Systems - Neetika Soni; Vinit Grewal (Revista Electronica de Veterinaria, 2022)
The recent developments in tele-healthcare services has raised the concern over the management and security of biomedical data during its transmission and storage. This paper proposes an integrated approach of signal compression and encryption to resolve these issues. Signal compression is done using Adaptive Fourier Decomposition (AFD) technique that decompose the Electrocardiogram (ECG) signal in terms of adaptively selected Basis functions instead of fixed Basis functions used in other decomposition techniques. Further chaotic maps are employed to encrypt the AFD coefficients. The performance of the integrated approach is evaluated in terms of distortion parameters such as PRD, PSNR and SNR while Compression Ratio (CR) and Quality score are used to measure compression efficiency. The results show that the proposed technique is efficient as compared to the state of the art techniques.